INTEGRATING â€œENGLISH PRONUNCIATIONâ€ APP INTO PRONUNCIATION TEACHING: HOW IT AFFECTS STUDENTSâ€™ PARTICIPATION AND LEARNING - Haryadi, S, Haryadi; Aprianoto, Aprianoto (JOLLT Journal of Languages and Language Teaching, 2020)
This study aimed to find out whether the integration of the English Pronunciation app in pronunciation class at Mandalika University of Education (UNDIKMA) can increase students? participation and self-learning. This study made use of quasi-qualitative design. Forty-eight first-year English department students from two groups of learning involved in this research, aged between 19 to 21. Each group, group A and group B, comprised of 24 students. Both groups received instruction using the English pronunciation app. Data was collected using class observation and interviews. In conducting observation, the observer chose to take the role of participant-observer in that the researcher immersed with the students during the observation activities. One volunteer assistant was employed to work with the researcher. It was intended to increase the accuracy of the data collected. In regard to the interview process, the researcher used individual and group interviews where one interviewer/researcher interviews a group of students. The result of the study indicates that the integration of the English Pronunciation app in teaching pronunciation increased the students? participation (engagement, attitude, and conduct). In addition, the app brought a positive effect to the establishment of independent learning to a significant number of students.